Nutritional status and height, weight and BMI centiles of school-aged children and adolescents of 6–18-years from Kinshasa (DRC). (18th August 2017) - Buhendwa, Rudahaba Augustin; Roelants, Mathieu; Thomis, Martine; Nkiama, Constant E.
Abstract: Background: The last study to establish centiles of main anthropometric measurements in Kinshasa was conducted over 60 years ago, which questions its current adequacy to describe or monitor growth in this population. Aim: To assess the nutritional status of school-aged children and adolescents and to estimate centile curves of height, weight and body mass index (BMI). Subjects and methods: A representative sample of 7541 school-aged children and adolescents (48% boys) aged 6–18 years was measured between 2010–2013. Smooth centiles of height, weight and BMI-for-age were estimated with the LMS method and compared with the WHO 2007 reference. Nutritional status was assessed by comparing measurements of height and BMI against the appropriate WHO cut-offs. Results: Compared to the WHO reference, percentiles of height and BMI were generally lower. This difference was larger in boys than in girls and increased as they approached adolescence. The prevalence of short stature (< –2 SD) and thinness (< –2 SD) was higher in boys (9.8% and 12%) than in girls (3.4% and 6.1%), but the prevalence of overweight (> 1 SD) was higher in girls (8.6%) than in boys (4.5%). Conclusion: Children from Kinshasa fall below WHO centile references. This study established up-to-date centile curves for height, weight and BMI by age in children and adolescents. These reference curves describe the current status of these anthropometric markers and can be used as a basis for comparison in future studies.